Assessing psychosocial risk in pediatric cystic fibrosis. Issue 9 (25th June 2019) - Filigno, Stephanie S.; Miller, Jamie; Moore, Susan; Peugh, James; Weiland, Jeanne; Backstrom, Jessica; Borschuk, Adrienne
Abstract: Background: Psychosocial risk factors are known to impact quality of life, treatment adherence, and health outcomes. No standardized comprehensive psychosocial risk screener is routinely utilized in cystic fibrosis (CF) care. The objectives of the study were to describe the range and severity of psychosocial risk within this CF population, investigate the reliability of a comprehensive psychosocial screener in pediatric CF clinical care, and explore relationships between psychosocial risk and key factors affecting health outcomes. It was hypothesized that the PAT‐CF total and subscale α coefficients would be similar to those found in other pediatric medical populations. Method: Parents of 154 children with CF completed a CF‐specific version of the Psychosocial Assessment Tool_All‐lit (PAT‐CF), an empirically‐based psychosocial risk assessment, during routine CF clinical care. Results: The internal consistency of the PAT‐CF Total score was 0.71. Total score and subscale reliabilities reflect findings in other pediatric populations. Total risk scores fell in the following categories: 7% (Clinical‐highest risk), 41% (Targeted), and 52% (Universal‐lowest risk), respectively. Increased psychosocial risk was associated with Medicaid status and lower parent education, whereas having private insurance was associated with decreased psychosocial risk. Conclusions: The PAT‐CF can feasibly be used as an empirically‐based comprehensive psychosocial risk tool in routine CF care and is acceptable by parents. In addition to providing universal anticipatory guidance regarding child and family wellness, early identification of risk factors allows care teams to proactively provide targeted support and intervention for specific psychosocial risk factors to promote improved quality of life and ability to sustain daily care.